The Relationship Between Personal Protective Equipment Use and Reduction in Workplace Injuries - Venny Yusiana; Muchlisinalahuddin; Martanto; Fandel Maluw; Daisy Debora Grace Pangemanan (CV. Get Press Indonesia, 2025)
This study investigates the relationship between the use of Personal Protective Equipment (PPE) and the reduction of workplace injuries among workers at PT X. Using a quantitative research design with a pre-test and post-test survey approach, data were collected from 110 respondents selected through purposive sampling. The results demonstrated a significant decrease in workplace injuries after the implementation of PPE, with the average injury score dropping from 2.27 before PPE use to 1.50 after PPE use (p-value = 0.000). These findings indicate that the use of PPE is highly effective in reducing both the frequency and severity of workplace injuries. Factors such as worker discipline, awareness, and knowledge significantly influence the effectiveness of PPE use. The study concludes that consistent and proper use of PPE, supported by worker education and the availability of quality equipment, can substantially enhance workplace safety and reduce occupational health risks